Performance Assessment of Branch Office Assistant (KCP) Leaders Using the Simple Additive Weighting Method - Wibowo, Dwi; Astuti, Femi Dwi; Astuti, Yuli; Widayani, Wiwi; Fauzi, Arma (LPPM UTDI (d.h STMIK AKAKOM) Yogyakarta, 2024)
Abstract— Performance Appraisal is a process that allows organizations to know, evaluate, measure and assess the performance of their members appropriately and accurately. This activity is closely related and influences the effectiveness of the implementation of human resource activities in the company, such as promotion, compensation, training, career management development and others. This is because the performance appraisal function can provide important information to the company to improve decisions and provide feedback to employees about their actual performance.The implementation of the achievement and performance appraisal of KCP leaders at KSPPS Tunas Artha Mandiri Nganjuk Branch has so far still used manual and has not used a decision support sistem so that the data generated is not accurate and takes a long time. As a result, if used in decision making, it is not appropriate and causes problems such as non-transparent management, decreased quality and performance of KCP leaders. The author applies and implements the Additive Weighting method (SAW) to measure the achievement and performance assessment of the Sub-Branch Office leadership at KSPPS Tunas Artha Mandiri Nganjuk Branch. With the aim of this decision support sistem can provide information and recommendations as well as accurate and efficient performance appraisal data.Keywords-Decision Support Sistem, Simple Additive Weighting, Employee Appraisal